Research progress and prospects for constructing ecological security pattern based on ecological network - Xu Dong; Fang Wang; Meichen Fu (Ecological Indicators, 2024)
As global ecological problems become increasingly prominent, the construction of ecological security pattern (ESP) has become particularly important for ensuring regional ecological security, coordinating social and economic development, and improving the livelihood and well-being of people. ESP construction based on source-resistance surface-corridor-node information has become the main research paradigm. In this study, the literature analysis method is employed to obtain relevant ESP research results systematically from the perspectives of conceptual connotations, construction methods, evaluations and regulations. The conclusions are as follows: (1) Over time, dynamic pattern construction has become a research hotspot; spatially, less attention has been given to areas with multi-scale and cross-administrative boundary. (2) The ESP construction method is relatively mature, but shortcomings remain, such as the neglect of small-scale but important ecological sources, insufficient consideration of species living habits, lack of research on corridor heterogeneity, and inadequate field surveys and visits. (3) Qualitative ESP evaluation focuses on analyzing the rationality and accuracy of the delineated ecological sources. In contrast, quantitative ESP evaluation focuses on the connectivity, accessibility and robustness of ecological network (EN), which has been more widely applied. Multilevel regulation can promote the implementation of ESP. Future research should focus on (1) selecting ecosystem services on the basis of local conditions and considering trade-offs and synergistic relationships, (2) deepening research on the spatiotemporal evolution of ecosystem services and accurate construction of EN, and (3) introducing machine learning to achieve intelligent ESP construction. This paper provides directions for future research, outlines new ideas for the systematic and rigorous construction of ESP and promotes more in-depth and practical global ecological civilization construction.